Retrievable Z-Stents for the Treatment of Refractory Corrosive Esophageal Strictures in Children - Zheng, Jiahe; Chang, Zhihui; Liu, Zhaoyu; Lu, Zaiming; Zhao, Jian; Ma, Yujia; Zhang, Jun; Wang, Chuanzhuo; Guo, Qiyong (European Journal of Pediatric Surgery, 2015)
Introduction The use of retrievable esophageal stents represents a new method to avoid multiple dilations for stenosis recurrence. The aim of this study was to evaluate the efficacy of treatment with a retrievable covered Z-stent for corrosive esophageal stenosis in children.Materials and Methods A total of 15 children were enrolled in this study. All patients had undergone balloon catheter dilatation (BCD) but without significant symptomatic improvement. A retrievable Z-stent was placed, and the dysphagia score was evaluated. After stent removal, healing was considered to have occurred if the score was 0 to 1 for at least 12 continuous months.Results Stents were placed in all children without complications and were later removed successfully. Stents remained in situ for 4 to 8 weeks (mean, 7.4 weeks). Dysphagia scores decreased from 3 to 4 to 0 to 1 in all patients while the stent was in place. During the 12-month follow-up period, seven patients remained free from dysphagia, but eight children had recurrent stenosis and required a subsequent BCD to alleviate symptoms from the stricture. Six of them required placement of a second stent.Conclusions The use of a retrievable Z-stent is an effective method and may become the treatment of choice for corrosive esophageal stenosis in children.
Keywords: retrievable; stent; corrosive; esophageal stenosis; children